Overview of Knowledge Level and Status of Oral Hygiene in Aceh Besar State Elementary School Students - Niakurniawati; Herry Imran (Community Medicine and Education Journal, 2023)
Teaching children about the importance of dental and oral hygiene from an early age is a long-term investment in their health. Parents and caregivers have an important role in guiding children to maintain regular dental and oral hygiene. Good dental care habits should be taught from an early age, including brushing teeth twice a day, using age-appropriate fluoride-containing toothpaste, flossing teeth, and visiting the dentist regularly. This study aimed to provide an overview of aspects of knowledge and status of students' dental and oral hygiene in state elementary schools in Aceh Besar, Indonesia. The descriptive observational study, where as many as 44 research subjects participated in this study. Observation of knowledge and oral health status was carried out univariately using SPSS. In conclusion, the knowledge of Aceh Besar, state elementary school students, is still relatively poor regarding oral health. The dental and oral health status of Aceh Besar state elementary school students is classified as moderate.